Pemikiran Politik Ahmad Khan - Masykur Hakim (Refleksi: Jurnal Kajian Agama dan Filsafat, 2002)
Ahmad Khan was a multifaceted figure, recognized as a reformer, thinker, educator, and politician. His religious reformist ideas sparked both praise and criticism within the Muslim community of India. While respected as an intellectual and educator, his views were often seen as controversial. Scholars such as Rajmohan Gandhi and Abdul Hayy Hasan an-Nawdiy acknowledged his intelligence and courage but questioned his depth of Islamic knowledge and personal religious observance. Despite these critiques, Ahmad Khan made significant contributions to political and Islamic thought in 19th-century India. While his reforms in religion, society, and education are well-documented, his political thought remains underexplored. This paper aims to shed light on his political ideas and role as a politician.